Phytochemical Screening for Phenol and Optimizing the SNEDDS (Self-Nanoemulsifying Drug Delivery System) Formula Using the Simplex Lattice Design Method on Curcuma caesia Roxb Rhizome Extract - Sholichah Rohmani; Okid Parama Astirin; Soerya Dewi Marliyana; Nestri Handayani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to screen the phytochemistry of phenol and optimize the formulation of Curcuma caesia Roxb. rhizome extract, which is difficult to dissolve in water, in the form of Self-Nanoemulsifying Drug Delivery System (SNEDDS) using the simplex lattice design method. The phenol content was identified using thin-layer chromatography,and the compound levels were determined spectrophotometrically. An initial screening was conducted to determine the oil phase, surfactant, and co-surfactant to use. The characterization of SNEDDS in the optimal formula includes transmittance, particle size, and polydispersity-index (PI). Olive oil, Tween 80,and polyethyleneglycol (PEG)-400 are the oil phase, surfactant, and co-surfactant selected due to the highest ability to dissolve Curcuma caesia Roxb.rhizome extract. The results of phytochemical screening of the polyphenol compound group using thin-layer chromatography produced spots with an Rf value of 0.76 and a phenol content of 61.823 mgGAE/g. The optimization results showed that the optimal formula was obtained at a composition of 1:8:1 for olive oil, Tween 80, and PEG-400. The SNEDDS of C.caesia Roxb.rhizome extract produced a nanoemulsion with a loading dose of 250 mg/5 g SNEDDS, a transmittance of 98.6%, a particle size of 14.1 nm, and a polydispersity index (PI) of 0.363.